Design Of A Fiber Optic Sensor-Based Respiration Monitoring System - Qulub, Fitriyatul; Alvie Aditya, Shabrina; Ama, Fadli; Pramudita Putra, Alfian (SEAN Institute, 2024)
Human breathing rate is an essential marker for assessing one's health, especially regarding respiratory issues. Precise breathing measurements are vital in medicine as they help detect problems early and devise effective treatment plans. The use of fiber optic sensors to monitor breathing offers excellent potential in health monitoring, both medically and independently. Such sensors have advantages such as ease of manufacturing, high sensitivity, compact size, and affordable cost. In this study, a Singlemode-Multimode-Singlemode (SMS) optical fiber-based breathing sensor was designed by fitting it as a belt around the abdomen to measure abdominal breathing. This SMS sensor has variations in multimode length and wavelength used. Tests were conducted in sitting and standing positions, and the results showed the best performance of the SMS sensor at a multimode length of 3.5 cm with an accuracy rate of 99.2525%, linearity of 0.9997, and sensitivity of 2.9725 Hz/dBm. In addition, the standing body position provides 96.5% accuracy with a multimode length of 3.5 cm, while the sitting position provides 96.8% accuracy with a multimode length of 2 cm.